2021
DOI: 10.1007/s40135-021-00271-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SARS-CoV-2 on Ocular Surface Pathology and Treatment Practices: a Review

Abstract: Purpose of ReviewThe ocular surface is a potential site of ocular involvement by SARS-CoV-2 infection. We performed a review of the literature to understand the pathogenesis of SARS-CoV-2 disease manifestations on the ocular surface as well as to elucidate emerging treatment patterns and practice changes during the COVID-19 pandemic. Recent Findings The ocular manifestations of SARS-CoV-2 are likely limited to a mild and transient conjunctivitis. Other manifestations have not been validated in larger cohorts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…It was unclear if any of these patients subsequently developed respiratory symptoms or had a poor visual outcome. However, previous studies have shown that most SARS-CoV-2 associated outpatient conjunctivitis cases appeared mild [1] and the majority of patients’ symptoms resolved within 3 weeks [5] . Similar to many places around the world, clinical studies were placed on hold during the surge, as was the case at the Aravind Eye Center.…”
Section: Limitationsmentioning
confidence: 89%
See 1 more Smart Citation
“…It was unclear if any of these patients subsequently developed respiratory symptoms or had a poor visual outcome. However, previous studies have shown that most SARS-CoV-2 associated outpatient conjunctivitis cases appeared mild [1] and the majority of patients’ symptoms resolved within 3 weeks [5] . Similar to many places around the world, clinical studies were placed on hold during the surge, as was the case at the Aravind Eye Center.…”
Section: Limitationsmentioning
confidence: 89%
“…SARS-CoV-2 RNA has been detected in the conjunctiva and tears of patients hospitalized with moderate to severe COVID-19 disease. [1] , [2] Conjunctivitis associated with COVID-19 disease is documented in both the outpatient and hospitalized populations, although the prevalence varies dependent on the study and population investigated and it remains a debate whether infection with SARS-CoV-2 can present as a primary conjunctivitis [ 1 , [3] , [4] , [5] , [6] ].…”
Section: Introductionmentioning
confidence: 99%
“…Bal et al suggest that ocular manifestations can appear at any stage of the disease, with conjunctivitis often being an early sign, while later ocular pathology may be linked to more severe COVID-19. Although the evidence for direct transmission through eye mucosa is currently lacking, early detection of COVID-related ocular symptoms could potentially limit disease spread [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Positivity rate in ocular surface samples of COVID-19 patients is likely dependent on the stage of the disease at the time of corneal retrieval and the retrieval technique [ 10 ]. Likewise, highly variable prevalence of ocular lesions in patients affected by SARS-CoV-2 are also reported, ranging from 0.8% to 31.6% [ 11 12 ]. Thus, the available data provide only limited and conflicting evidence to support a possible SARS-CoV-2 infection via the corneal or conjunctival route.…”
Section: Introductionmentioning
confidence: 99%